2004
DOI: 10.1152/ajpcell.00483.2002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic organization in vascular smooth muscle: distribution and localization of caveolin-1 and phosphofructokinase

Abstract: We have shown that a compartmentation of glycolysis and gluconeogenesis exists in vascular smooth muscle (VSM) and that an intact plasma membrane is essential for compartmentation. Previously, we observed that disruption of the caveolae inhibited glycolysis but stimulated gluconeogenesis, suggesting a link between caveolae and glycolysis. We hypothesized that glycolytic enzymes specifically localize to caveolae. We used confocal microscopy to determine the localization of caveolin-1 (CAV-1) and phosphofructoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…The demonstration that CAV-1 functions as a scaffolding protein for the membrane recruitment of PFK is a very important step in elucidating the physical basis for glycolytic-membrane interactions and their role in the organization of carbohydrate metabolism as observed in our previous studies on VSM (59). Moreover, our studies are consistent with studies that have demonstrated that CAV-1 coimmunoprecipitates with PFK-M from 293T cells transiently overexpressing V5-tagged PFK-M (34).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The demonstration that CAV-1 functions as a scaffolding protein for the membrane recruitment of PFK is a very important step in elucidating the physical basis for glycolytic-membrane interactions and their role in the organization of carbohydrate metabolism as observed in our previous studies on VSM (59). Moreover, our studies are consistent with studies that have demonstrated that CAV-1 coimmunoprecipitates with PFK-M from 293T cells transiently overexpressing V5-tagged PFK-M (34).…”
Section: Discussionsupporting
confidence: 90%
“…In vascular smooth muscle, a compartmentation of glycolytic metabolism has been well established, and the role of caveolae in the compartmentation has been proposed (1). We have found previously that PFK appeared to colocalize with a fairly ubiquitous plasma membrane protein named caveolin-1 (CAV-1), consistent with a role for CAV-1 as an anchor for glycolysis to the plasma membrane (59). However, colocalization with confocal microscopy simply implies that two proteins are in close proximity.…”
Section: Discussionmentioning
confidence: 58%
“…These recent studies have suggested that the mechanism of ouabain activation occurred through protein-protein interactions that had been previously shown for cardiac muscle and kidney epithelial cells (17,27,47). However, the cascade activates an hypertrophic pathway in cardiomyocytes and a proliferative pathway in the kidney cells.…”
Section: Discussionmentioning
confidence: 77%
“…The compound ␤-methyl-cyclodextrin has been shown to deplete membrane cholesterol (14,47). Thus if treatment of VSMCs would prevent the specific ouabain activation of ERK1/2, this would certainly lend credence to the suggestion that ouabain is activating the cascade via an interaction with a specific population of ␣ 1 -subunits.…”
Section: Colocalization Of Namentioning
confidence: 93%
“…K ATP channel microenvironment has been considered to be different from "bulk" cytosol as these channels exist in multimolecular complexes with [34][35][36][37][38] and are functionally regulated by many metabolic enzymes [39,40]. Glycolytic enzymes are specifically localized to caveolae [41]. It's been suggested that subsarcolemmal ATP may play an important role in activation of K ATP channels at relative high intracellular ATP [42].…”
Section: Discussionmentioning
confidence: 99%